c-fos-induced growth factor/vascular endothelial growth factor D induces angiogenesis in vivo and in vitro - Marconcini, Lucia (The National Academy of Sciences, 1999)
c-fos-induced growth factor/vascular endothelial growth factor D (Figf/Vegf-D) is a secreted factor of the VEGF family that binds to the vessel and lymphatic receptors VEGFR-2 and VEGFR-3. Here we report that Figf/Vegf-D is a potent angiogenic factor in rabbit cornea in vivo in a dose-dependent manner. In vitro Figf/Vegf-D induces tyrosine phosphorylation of VEGFR-2 and VEGFR-3 in primary human umbilical cord vein endothelial cells (HUVECs) and in an immortal cell line derived from Kaposi’s sarcoma lesion (KS-IMM). The treatment of HUVECs with Figf/Vegf-D induces dose-dependent cell growth. Figf/VEGF-D also induces HUVEC elongation and branching to form an extensive network of capillary-like cords in three-dimensional matrix. In KS-IMM cells Figf/Vegf-D treatment results in dose-dependent mitogenic and motogenic activities. Taken together with the previous observations that Figf/Vegf-D expression is under the control of the nuclear oncogene c-fos, our data uncover a link between a nuclear oncogene and angiogenesis, suggesting that Figf/Vegf-D may play a critical role in tumor cell growth and invasion.